PENGEMBANGAN EMOSI POSITIF DALAM PENDIKAN ISLAM PERSPEKTIF NEUROSAINS - Apri Wulandari; Suyadi Suyadi (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
It turns out that emotional intelligence that is not ready will hinder in accepting the chase from the teacher, this article intends to present a way of knowing how to process the emotional intelligence of students. Emotion is a person's ability to recognize and understand themselves and others. Emotions are used in establishing interpersonal relationships as well. For this reason, the emotions, especially in the education system are able to facilitate the achievement of values conveyed in the educational process which cannot be separated from the interaction between students and educators or with other students. In the perspective of neuroscience, emotional intelligence is produced by the frontal cortex where there is a meeting of emotions. Cognition is regulated by the limbic system. Each of these structures also has different functions. Therefore, maximizing each function contained in the human brain including emotional functions should be applied in the learning system.It turns out that emotional intelligence readiness is needed in accepting learning, making it easier to receive material delivered by an educator. The virtue or excellence of a teacher in learning emotions in PAI learning in the perspective of neuroscience is that students become happy to learn. Joy arises because brain-based learning is able to activate the brain when it starts learning like a light switch on the "on" position, which means it's ready for the brain's memory to be ready.